Green open space plan for coal mine reclamation area PT Angsana Jaya Energi, Angsana, Tanah Bumbu, South Kalimantan - Febrianti, Aulia Nur; Mardiyanto, Agus; Susiloningtyas, Arianik; Made, Dewa; Darmastuti, Dwi Reping; Sugih, Yuvita (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Mining activities can have a significant negative impact on the environment, leading to degradation. Converting land into a mining area requires mandatory post-mining reclamation activities. PT Angsana Jaya Energi, one of the coal mining companies in South Kalimantan, especially in Tanah Bumbu Regency, is participating in the implementation of reclamation activities. These activities will develop urban forests on mining land sold, covering an area of 29.75 hectares based on field surveys and data synthesis. To prepare a zoning plan for an urban forest area, several analyses are necessary, including spatial requirements, activities, user characteristics, forest organization, and regional footprint. The development of an urban forest will serve different functions in each area.